(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The diversity of AI-powered m-Health technologies creates challenges for their effective regulation. This, in turn, enhances the risk of potential harms for the patients, including discriminatory outputs. This paper submits that algorithms embedded in m-Health technologies are particularly likely to discriminate against patients based on a unique synergy of protected grounds, reinforcing intersectional patterns of disadvantage. Based on the analysis of Section 1557 of the Patient Protection and Affordable Care Act, the main US non-discrimination provision applicable in the area of healthcare, the contribution highlights regulatory gaps in the protection of intersectional claimants who face automated discrimination. Lastly, the paper critically analyzes the Biden Administration’s latest proposal for the revised Section 1557 rule, focusing particularly on a new provision dealing with algorithmic discrimination in healthcare.